Intensified Downstream Processing of Monoclonal Antibodies Using Membrane Technology. Issue 3 (19th October 2020) - Nadar, Sathish; Shooter, Gary; Somasundaram, Balaji; Shave, Evan; Baker, Kym; Lua, Linda H. L.
Abstract: The need to intensify downstream processing of monoclonal antibodies to complement the advances in upstream productivity has led to increased attention toward implementing membrane technologies. With the industry moving toward continuous operations and single use processes, membrane technologies show promise in fulfilling the industry needs due to their operational flexibility and ease of implementation. Recently, the applicability of membrane‐based unit operations in integrating the downstream process has been explored. In this article, the major developments in the application of membrane‐based technologies in the bioprocessing of monoclonal antibodies are reviewed. The recent progress toward developing intensified end‐to‐end bioprocesses and the critical role membrane technology will play in achieving this goal are focused upon. Abstract : The biopharmaceutical industry is exploring various approaches to intensify downstream processing of monoclonal antibodies to meet the increasing demand for antibody‐based drugs and the improvement in upstream productivity. The review focuses on recent advances in membrane technology and their roles in monoclonal antibodies downstream process intensification.